2015
DOI: 10.4314/star.v3i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risks and Uncertainties in Poultry Farming in Kwara State, Nigeria

Abstract: Article InformationThis study was designed to assess the risks and uncertainties encountered by poultry farmers in Kwara State, Nigeria. Specifically, the study describes the socio-economic characteristics of the farmers, identify the risks and uncertainties encountered by the farmers, determines the level of severity of the risks and uncertainties, and identifies the coping strategies employed by the farmers. Primary data obtained from 99 registered poultry farmers selected through multistage sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…The rate of the reaction increased appreciably with increase in temperature as shown in Table 3. The observed positive temperature effect is like that of Banjoko et al [1] in the uncatalyzed reaction of phenyl-2,4,6trinitrophenyl ether with CHA in benzenemethanol mixtures, though in this reaction the addition of methanol produced remarkable decrease in rate. Hydrogen bonds are known to be weakened with an increase in temperature, hence an increase in rate with an increase in temperature is expected on addition of ethanol for reactions that are not base catalysed.…”
Section: Effect Of Temperaturesupporting
confidence: 78%
See 2 more Smart Citations
“…The rate of the reaction increased appreciably with increase in temperature as shown in Table 3. The observed positive temperature effect is like that of Banjoko et al [1] in the uncatalyzed reaction of phenyl-2,4,6trinitrophenyl ether with CHA in benzenemethanol mixtures, though in this reaction the addition of methanol produced remarkable decrease in rate. Hydrogen bonds are known to be weakened with an increase in temperature, hence an increase in rate with an increase in temperature is expected on addition of ethanol for reactions that are not base catalysed.…”
Section: Effect Of Temperaturesupporting
confidence: 78%
“…For a reaction that is not base-catalysed and occurs in the presence of small amounts of methanol in non-polar aprotic solvent, Scheme 3 [1] applies. Application of the steady-state hypothesis to Scheme 3, working in terms of the stoichiometric base concentration, gives the observed overall second-order rate constant, k A as shown in Eq.…”
Section: Mechanism Of the Uncatalysed Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marketing chain was a problem in egg distribution to consumers, since the length of the chain could cause decreasing egg quality as well as damage in the transportation process. Banjoko et al (2014) stated that good transportation in marketing could reduce egg damage which has an impact on sales volume. The collaboration model, coaching model, and the principle of cooperation in the smallholder layer farming business were still limited.…”
Section: Description Of Respondents Of the Smallholder Layer Farmersmentioning
confidence: 99%
“…Despite the fact that the country's poultry industry is extremely fragmented with most of the birds being raised in 'backyards' or on poultry farms with less than 1,000 birds, the number of researches conducted (e.g. Ajetomobi and Binuomote, 2006;Salman et al, 2010;Banjoko et al, 2014) has demonstrated the importance of the sub-sector to the economy of the country.…”
Section: Introductionmentioning
confidence: 99%